Unfair competition by misrepresentation and the legal protection against it in Belarus - Maskayeva, Natalia G. (Journal of the Belarusian State University. International Relations, 2023)
The author of the article analyses provisions against unfair competition by misrepresentation contained in the Paris convention for the protection of industrial property of 20 March 1883, the Treaty on the Eurasian Economic Union of 29 May 2014, and the domestic legislation of the Republic of Belarus. It is shown that the Republic of Belarus has duly implemented its obligations under these treaties. Changes are proposed to art. 26 of the Law of the Republic of Belarus of 12 December 2013 No. 94-З “On counteracting monopolistic activitity and promoting of competition” to cover actual and potential misrepresentation, as that would strengthen the preventative function of domestic legislation on unfair competition. It is also suggested that a complete list of remedies be included in art. 1030 of the Civil Code of the Republic of Belarus of 7 December 1998, to enhance legal certainty and the balance of public and private interests. Furthermore, it is argued that in establishing a fact of misrepresentation, the relevant authorities should determine that at least 20–25 % of consumer respondents in sample polls find a statement or representation actually or potentially misleading. Relevant changes are suggested to the Recommended practices for determining violations of anti-monopoly legislation concerning unfair competition and a prospective Resolution of the Plenum of the Supreme Court of the Republic of Belarus on adjudication of Belarusian courts in unfair competition.
Keywords: art. 10-bis of the Paris convention for the protection of industrial property; common rules and principles of competition; unfair competition; unfair competition by misrepresentation; violation of anti-monopoly legislation